Mobile grammar application for computer students in higher vocational education: Self-learning tool to enhance student's autonomy - Gusti Nyoman Ayu Sukerti; Luh Nyoman Chandra Handayani; I Putu Yoga Laksana; Gary P. Boyce (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2023)
The research aims to analyze and develop a mobile-based grammar learning application and the perceptions of computer vocational high school students regarding the use of the application in the learning process. The main focus of this research is developing a mobile-based grammar application for computer users, which enhances students' independence in the grammar teaching process, along with examining how the application was put into practice. This learning media was created using the ADDIE Model, which includes analysis, design, development, implementation, and evaluation. The waterfall method, dart programming language, and Flutter framework are used to create the application. After the implementation stage, this research used a mixed methods approach, combining quantitative and qualitative survey data collected through Google Forms with Likert Scale and paragraph question types. The findings from this study shed light on the needs, attitudes, preferences, and feedback from students for improvement regarding the utilization of mobile grammar apps for language learning. The analysis shows that students have a positive experience when learning grammar using this app, as it allows them to extend their learning beyond the classroom without time and place restrictions. The data analysis provides valuable insights into the effectiveness and potential drawbacks of integrating such apps into the curriculum. These insights contribute to the ongoing discourse on technology integration in education and offer practical implications for educators, curriculum designers, and educational policymakers who want to improve language teaching through digital devices in vocational high schools.